Memotret Cara Berpikir dari Teori Mental Self-Government (Sebuah Studi Validasi Lintas-Budaya) - Aditomo, Anindito (Faculty of Psychology, Universitas Surabaya, 2005)
This article reports the results of a literature review and empirical investigation to evaluate the cross-cultural internal validity of the Thinking Styles Inventory and the mental self-government theory (Sternberg, 2002), which is influential but also criticized as based on a weak construct. The main question was whether the interrelationships between thinking styles and the underlying factor structure consistent with the mental self-government theory. This question was investigated using correlational analysis and factor analysis of data from 562 undergraduate students from five faculties in the University of Surabaya. The latent factors obtained were not consistent with its theory. Results also pointed out to other weaknesses of the inventory and theory, including the issue of bipolarity and contextual nature of thinking styles. As an alternative, two new dimensions or types of thinking are proposed: the creative-critical and the practical-conformist thinking styles. Tulisan ini melaporkan hasil kajian pustaka dan penelitian empiris untuk mengevaluasi validitas internal lintas-budaya Inventori Gaya Berpikir dan teori mental self-government (Sternberg, 2002), yang di satu sisi cukup berpengaruh, namun di sisi lain dipandang memilii konstruk yang lemah. Pertanyaan utama dalam studi ini adalah: apakah gaya berpikir saling terkait dan memiliki dimensionalitas sesuai logika teori mental self-government (MSG)? Pertanyaan ini dijawab melalui analisis korelasional dan faktor atas data dari 562 mahasiswa lima fakultas di Universitas Surabaya. Faktor laten yang muncul tidak sejalan dengan yang diajukan oleh teori MSG. Hasil analisis juga memberi petunjuk pada beberapa kelemahan lain teori dan alat ukur ini. Sebagai altematif, dimunculkan dua tipe atau dimensi baru, yakni polaberpikir kreatif-inovatif dan pola berpikir praktis-konformis.